MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN GUNA MENGURANGI KEMISKINAN DI DESA JE’NETALLASA KABUPATEN GOWA - Damayanti, Ratna Ayu; Syarifuddin, Syarifuddin; Haerial, Haerial (UNIVERSITAS PGRI MADIUN, 2020)
Abstract. Je'netallasa Village, Pallangga Sub-district, Gowa Municipality has made the community as a subject of development, no longer as an object of development in accordance with the